PENGARUH CYBER SECURITY DALAM KAMPANYE MALWARE KOREA UTARA: KETEGANGAN KOREA UTARA DAN KOREA SELATAN (Triwikrama: Jurnal Ilmu Sosial, 2025)
This research examines cyber security in the recent tensions between North Korea and South Korea, the author analyses that cybercrime is included in international security and interest issues. The author uses descriptive qualitative methods through secondary data analysis from journals, news, and official reports. This research reveals that North Korea has conducted cyber attacks on South Korea 3 times within 15 years which can cause damage especially in the digital world. his request. North Korea can use cyber warfare to exploit weaknesses in its enemies' systems or any item that can fulfil its demands. South Korea's response to the state of cyber warfare cannot and should not be seen in isolation from the larger security system. It should be underlined that even if South Korea decides to respond to a cyber warfare situation, it should not be seen in isolation from the larger security system.